(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article aims to defend a methodological position of using queer sources to study non-binary projects in fashion. It presents some concepts from queer and decolonial theory to analyze the binary and non-binary of fashion, thinking from Lauretis (19941987), Butler (2012[1990]), Foucault (1988) and Vergueiro (2018). Next, we propose a qualitative approach from a case study, analyzing the narratives of fashion designer Fabio Costa and artist and fashion designer Vicenta Perrotta, with the objective of examining their non-binary fashion productions. Among the results, we identified that personal experience and their trajectory as LGBTQIAPN+ are reflected in the fashion and dress productions of these creators, therefore, besides being an object of study, they also became an epistemological source for research in non-binary fashion.